Inside Cover: Electrodeposition of Protocrystalline Germanium from Supercritical Difluoromethane (ChemElectroChem 5/2016). Issue 5 (21st April 2016) - Cummings, Charles Y.; Bartlett, Philip N.; Pugh, David; Reid, Gillian; Levason, William; Hasan, Mahboba M.; Hector, Andrew L.; Spencer, Joe; Smith, David C.; Marks, Samuel; Beanland, Richard
Abstract : The Inside Cover Picture shows that the electrodeposition of Ge in supercritical CH2 F2 at 85 ºC from germanium (II) triiodide, the most readily reduced of the three trihalides studied, produces films containing nanocrystals of Ge embedded in an amorphous Ge film. More details can be found in the Full Paper by C. Cummings et al. onpage 726 in Issue 5, 2016 (DOI:10.1002/celc.201500539 ).